Community-Acquired Methicillin-Resistant Pyogenic Liver Abscess - Joel Cherian Medical Student; Rahul Singh MD; Muralidhar Varma MD; Sudha Vidyasagar MD; Chiranjay Mukhopadhyay MD (SAGE Publishing, 2016)
Pyogenic liver abscesses are rare with an incidence of 0.5% to 0.8% and are mostly due to hepatobiliary causes (40% to 60%). Most are polymicrobial with less than 10% being caused by Staphylococcus aureus . Of these, few are caused by methicillin-resistant Staphylococcus aureus (MRSA) and fewer still by a community-acquired strain. Here we present a case study of a patient with a community-acquired MRSA liver abscess. The patient presented with fever since 1 month and tender hepatomegaly. Blood tests revealed elevated levels of alkaline phosphatase, C-reactive protein, erythrocyte sedimentation rate, and neutrophilic leukocytosis. Blood cultures were sterile. Ultrasound of the abdomen showed multiple abscesses, from which pus was drained and MRSA isolated. Computed tomography of the abdomen did not show any source of infection, and an amebic serology was negative. The patient was started on vancomycin for 2 weeks, following which he became afebrile and was discharged on oral linezolid for 4 more weeks. Normally a liver abscess is treated empirically with ceftriaxone for pyogenic liver abscess and metronidazole for amebic liver abscess. However, if the patient has risk factors for a Staphylococcal infection, it is imperative that antibiotics covering gram-positive organisms be added while waiting for culture reports.